The Effect of Self Assessment Strategy on Students’ Writing Recount Text at Eight Grade of SMP Swasta Advent 5 Medan - Sahlan Tampubolon; Kammer Sipayung; Melvi Sagala (Merwin Publisher, 2023)
This study focused on the effect of self-assessment strategy on students’ writing recount text. The objective of this study was to know the effect of self-assessment on students’ writing recount text at eight grade. It was conducted by using experimental research design. The population of this study was the eight student of SMP Swasta Advent 5 Medan. Two classes were taken as the sample of this research. The class VIII-1 was as the experimental group and the class VIII-2 was as the control group. The experimental group was taught by using self-assessment strategy, while the control group was taught by traditional teaching method. The instrument of collecting data was writing test and field note. The result of this study shows that the use of self-assessment strategy is effective for students in writing recount text. From the result, the students’ score of the experimental group in the post-test was higher than the students in the pre-test. The mean score of post-test in the experimental group 76.55 was higher than mean score of the control group 60.88. It was really good significant effect by using self-assessment strategy. The data were analyzed by using t-test formula. The data were collected by giving pre-test and post- test. After giving the treatment, the result of paired sample t-test, obtained that sig. (2-tailed) or the p value was 0.00 from the df 34 and the significance level (α) is 0.05. Since 0.00 is smaller than significance level (α) 5%. The null hypothesis is rejected. In other word, the hypothesis saying that the mean after the treatment is smaller than before the treatment. It means that self-assessment strategy can be used as teaching approach alternative to enrich students writing at eight grade. Keywords: Self-Assessment Strategy, Recount text, Writing.